AGE LIMITS OF THE GREENSTONE BELTS OF THE WESTERN ALDAN SHIELD - Kotov A.B.; Anisimova I.V.; Glebovitsky V.A.; Kovach V.P.; Sal'nikova E.B.; Zagornaya N.Yu.; Smelov A.P.; Berezkin V.I. (My University, 2004)
The main features in the geological structure of the western Aldan Shield are largely determined by nearly meridional and NE-trending fault zones that host numerous tectonic fragments composed of weakly metamorphosed volcanosedimentary rocks of the Saimagan, Tarynakh, Tokko-Khanin, Itchilyakh, Evonokit, Temulyakit, Tungurcha, Yaelakh, Subgan, Bulgunyakhtakh, and Balaganakh greenstone belts. At present, most researchers believe that these tectonic fragments were formed during the Late Archean stage of the Aldan Shield evolution. However, reliable geochronological and isotopic-geochemical data are currently available only for the Tokko-Khanin greenstone belt. In order to fill this gap in our knowledge of the region, we performed Sm-Nd isotopic studies of clastic metasedimentary and metavolcanic rocks from the greenstone belts in the western Aldan Shield.